Comparison of the Response to Pulpal Sensibility Tests in Well-Controlled and Uncontrolled Type II Diabetes Mellitus Patients: A Cross-Sectional Study - Fatemeh Owlia; Faezeh Zarezadeh; Sara Jambarsang; Maryam Kazemipoor (Hindawi Limited, 2022)
Introduction. Diabetes mellitus is a metabolic disorder in which impairment of sensory fibers would be anticipated. The present study would assess the dental pulp response to cold and EPT sensibility tests in patients with type 2 diabetes, both well-controlled and uncontrolled. Materials and Methods. One hundred two maxillary central incisors, belonging to participants aged 35-67 years, were included in this survey. At last, 51 diabetic patients were allocated to each group of well-controlled (HbA1C < 7) and uncontrolled (HbA1C ≥ 7). Electric and cold pulpal vitality tests were conducted for all teeth. Statistical analysis was performed with Student's t-test, the chi-square test, and the multiple linear regression model. A P value less than 0.05 was considered significant. Results. Based on the results of this study, the mean value of response to EPT was 4.51 ± 2.06 and 4.41 ± 1.85 in well-controlled and uncontrolled diabetic patients, respectively. Also, the pulpal responses to cold and EPT tests had no significant differences between the two groups (P>0.05). Conclusion. Tooth responses to the cold and EPT sensibility tests were not different in well-controlled and uncontrolled diabetic patients. Despite no statistically significant correlation, male diabetic patients in the uncontrolled group showed a lower sensory response threshold to EPT compared to a well-controlled group.